Functional, Energy and Seismic Retrofitting in Existing Building: An Innovative System Based on xlam Technology. (December 2015) - Mora, Tiziano Dalla; Righi, Alessandro; Peron, Fabio; Romagnoni, Piercarlo
Abstract: In recent years significant investments were made in retrofitting of existing buildings with the aim to realize a strong functional, energy and seismic refurbishment. This is a complicated challenge: the technical and economic feasibility of intervention must be correctly defined and most of interventions are not standardized or coordinated or properly managed. Given the awareness related to environmental sustainability topics, this study focused on the development of systems and technologies based on the use of natural and environmentally sustainable materials. The paper is focused on the xlam panel that is integrated into an existing building (outside or inside the external wall) in order to improve the static and structural tightening. The system is designed for modularization and standardization for giving simplicity and speed of assembly and low cost providing also. Through a three-dimensional and numerical model, simulations were carried out to verify and to optimize the energy behavior of the chosen materials and to identify the best combination on thermal performance compared with the costs and environmental impacts of the product. The values and the results obtained were tested experimentally in the laboratory by the construction of a prototype.